Holistic and Component Separate Diagnosis of Mathematical Problem Solving Skills and Real-Life Connection Skills for Elementary School Students in Pattani Province - Masae, Suleeha; Lateh, Afifi; Sama-Ae, Areeyuth; Musor, Hamidah (Journal of Information and Learning [JIL], 2024)
This research aimed to diagnose mathematics problem-solving skills and real-life connection skills holistically and separately for primary school students in Pattani Province. The target groups consisted of 11 mathematics teachers in grades 5-6, selected through purposive sampling, and 463 students in grades 5-6 in the second semester of the academic year 2023. The research instruments included a survey questionnaire focusing on fraction problems and diagnostic tests for assessing mathematics problem-solving skills and real-life connection skills. Statistical analyses included percentages, means, and standard deviations. The findings revealed that students generally understood problem-solving skills were at a good level, with strengths in understanding the problem, planning, and concluding. However, the implementation of problem-solving strategies was at a moderate level. Students lacked a deep understanding of fractions, which hindered their ability to apply this knowledge to real-life situations. Additionally, they showed a limited understanding of other subjects. Overall, the ability to connect mathematics to various topics and daily life was good, but connections to other subjects were at a moderate level.